Ultrastructural-immunohistochemical evidence for a maturation defect of temperature-sensitive G31 vesicular stomatitis virus in murine spinal cord neurons. - Dal Canto, M C (1979)
Ultrastructural immunoperoxidase studies were done in spinal cords of mice infected with wild type vesicular stomatitis virus or its temperature-sensitive (ts) mutant G31. Infected neurons showed subplasmalemmal staining of viral antigen and staining of viral particles budding from the neuronal membrane in wild-type vesicular stomatitis virus infection, whereas diffuse membrane and cytoplasmic staining with no budding virus was observed in ts G31 infection. Such findings suggest rapid viral assembly and release of viral particles from cells infected with wild-type virus. In contrast, maturation of ts G31 appears defective, and this would lead to accumulation of viral antigen in the cytoplasm of infected cells. These results correlate with studies in neuroblastoma cells which investigated the growth cycles of wild type, ts G31, and the spinal cord isolate of ts G31 as well as the viral protein-synthetic capacity of these viruses.